Green Governments - Niklas Potrafke; Kaspar Wüthrich (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We examine how Green governments influence macroeconomic, education, and environmental outcomes. Our empirical strategy exploits that the Fukushima nuclear disaster in Japan gave rise to an unanticipated change in government in the German state Baden-Wuerttemberg in 2011. The incumbent rightwing government was replaced by a leftwing government led by the Green party. We use the synthetic control method to select control states against which Baden-Wuerttemberg's outcomes can be compared. The results do not suggest that the Green government influenced macroeconomic outcomes. The Green government implemented education policies that caused comprehensive schools to become larger. We find no evidence that the Green government influenced CO2 emissions, particulate matter emissions, or increased energy usage from renewable energies overall. An intriguing result is that the share of wind power usage decreased relative to the estimated counterfactual. Intra-ecological conflicts and realities in public office are likely to have prevented the Green government from implementing drastic policy changes.
Keywords: C33; D72; E65; H70; I21; Q48; Q58; 330; Green governments; partisan politics; synthetic control method; causal effects; Fukushima nuclear disaster; environmental policies; energy policies; renewable energies; comprehensive schools